7(3s+9)=279

Simple and best practice solution for 7(3s+9)=279 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7(3s+9)=279 equation:


Simplifying
7(3s + 9) = 279

Reorder the terms:
7(9 + 3s) = 279
(9 * 7 + 3s * 7) = 279
(63 + 21s) = 279

Solving
63 + 21s = 279

Solving for variable 's'.

Move all terms containing s to the left, all other terms to the right.

Add '-63' to each side of the equation.
63 + -63 + 21s = 279 + -63

Combine like terms: 63 + -63 = 0
0 + 21s = 279 + -63
21s = 279 + -63

Combine like terms: 279 + -63 = 216
21s = 216

Divide each side by '21'.
s = 10.28571429

Simplifying
s = 10.28571429

See similar equations:

| f(4)=2(4)-3 | | y^2=22.5(22.5-y) | | 4(-x+6)=21 | | 6(2l+5)=42 | | (u+1)*8=16 | | -2xsquared-5x=1 | | 2x+11y-4xi=14+16i | | 7(2x+3)=21 | | (2x+7)(5x-4)=0 | | (x+0.9)(x+2.6)=0 | | (2n-1)/3-1/2=17/2 | | (2n-1)/3-1/5=17/5 | | 4[x+2]=18 | | X^5-x^4-1=0 | | 6(x+8)-29= | | 191+13x=360 | | 15x-12=49 | | 140/2000 | | 16x^2-24x-23=0 | | 8(x+4)-3= | | b+40+b+26=9b+5 | | -2(5x+13)-2=-6(3x-2)-41 | | 3[x-1]=49 | | 5(z+4)+1=7-(z+4) | | 12x^2-30x+48=0 | | A^2+15+54=0 | | -7=9+4c | | x-6y=50 | | t/-4-11 | | 2n/3=20/2 | | 58=4-9x | | 4s+8s= |

Equations solver categories